The Values of Monotheism Education in the Character of Compulsory Twenty - Suryani, Ira; Harahap, Sri Wahyuni; Harahap, Hotmasarih; Lubis, Indah Syafiqah; Tanjung, Muhammad Husein (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This study aims to describe the values of tauhid in the character of compulsory twenty and to reveal and analyze the educational values of tauhid contained in the character of compulsory twenty. The methodology used in this research is a literature study concerning monotheistic books such as Kifāyat Al-Awam and also several articles related to this research. Meanwhile, the data analysis technique used in this research is a content analysis by understanding the meaning of content to obtain related conclusions. The values of tauhid education in the character of compulsory twenty: First, the nature of God's existence indicates that God exists and only God we worship. In this case, we believe that the existence of Allah oversees all our actions, whether it is good or bad, and kaunuhu bashirān. Second, the Oneness of Allah through His Wahdāniyat, Qudrat, Iradāt, and qiyāmuhu binnafsih characteristics. Third, being able to organize oneself and intending to perform worship only to Allah because Allah has the nature of the supreme Aliman, meaning that Allah knows whatever we intend even in our hearts.